Muslim Spirituality, Religious Coping, and Reactions to Terrorism Among Pakistani University Students - Khan, Ziasma Haneef (Journal of religion and health, 2016)
Pakistani Muslim university students (N = 207) displayed Personal Distress, Public Distress, and Personal Defeat Reactions to Terrorism. All three reactions predicted poorer mental health with Personal Defeat being especially disturbed in its adjustment implications. In line with the assumptions of coping theory, scores on the Negative Religious Coping Scale correlated positively with Personal Distress and with Personal Defeat. However, Positive Religious Coping, the spirituality of Muslim Experiential Religiousness, and the Intrinsic and Extrinsic Personal Religious Orientations exhibited positive rather than the expected negative linkages with Personal Distress and Public Distress. Muslim Experiential Religiousness moderated associations of Positive and Negative Religious Coping with Public Distress. When spirituality was high, these relationships were negative. When spirituality was low, they became positive. These data documented the negative impacts that terrorism can have on Pakistanis and suggested that Muslim religious commitments may have an important role to play in resisting those influences.